Субкатегория "половина" как семантический маркер медиативного типа культуры (на материале памятников восточнославянской письменности) - Коч, Н. В.; Коч, Наталя Володимирівна; Koch, N. V. (ВД "Гельветика", 2017)
Стаття присвячена лінгвокультурологічному аналізу категорії «міра» та її субкатегорій як семантичних маркерів медіативного типу культури. На матеріалі пам’яток писемності досліджується мовна презентація субкатегоріі «половина» в східнослов’янському культурному npocmopiXI—XVII cm.

The article is devoted to the linguocultural analysis of the category «measure» and its subcategories as semantic markers of the media type of culture. The linguistic presentation of the subcategory «half» in the East Slavic cultural space of the XI — XVII cen¬turies is investigated on the basis of the monuments of literature material.
Коч Н. В. Субкатегория "половина" как семантический маркер медиативного типа культуры (на материале памятников восточнославянской письменности) / Н. В. Коч // Одеський лінгвістичний вісник. – 2017. – Вип. 10. – Т. 2. – С. 30-34.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; тип культури; медіативна культура; категорія «міра»; субкатегорія «половина»; type of culture; media culture; category «measure»; subcategory «half»